Optimizing Patient Safety: Intravenous Smart Pump Usability in Acute and Critical Care. - Giuliano, Karen K.; McDaniel, Peggy; Baker, Dian (AACN Advanced Critical Care)
Large-volume intravenous (IV) smart pumps are used in acute and critical care to deliver IV fluids and medications with safety-enhancing features such as dose error reduction systems. Although these technologies offer improvements over manual administration, IV smart pumps are associated with high rates of medication errors, programming challenges, and usability issues. Alarm fatigue, interface complexity, and workarounds are common, with studies showing high error rates. The Elaine Marieb Center for Nursing and Engineering Innovation at the University of Massachusetts Amherst addresses these concerns through interdisciplinary research focused on IV smart pump usability, safety, and innovation. Real-world studies, US Food and Drug Administration recalls, and post-market issues underscore the urgent need for improved user-centered design and regulatory oversight. Collaboration between clinicians, engineers, and manufacturers is crucial for developing safer, more intuitive devices. This article synthesizes current evidence and highlights opportunities for advancing IV smart pump safety and usability to improve patient outcomes.